Optimalisasi pendinginan pasif dengan dual evaporator loop heat pipes: studi visualisasi dengan radiografi neutron - Fathoni, Andhy M.; Hendrayanto, Priska A.; Ramadhan, Ranggi S.; Putra, Nandy (BKS-TM Indonesia, 2024)
In this study, a dual evaporator loop heat pipe (DE-LHP) was developed to accommodate multiple heat sources from a single electronic device. Loop heat pipe (LHP) operation involves complex hydrody-namic phenomena, especially in scenarios involving numerous vapor-liquid interfaces. The complexity of LHPs depends on various elements, such as device design, orientation to gravity, selection of work-ing fluids, heat loads, and condenser cooling conditions. The accuracy of virtual representations in cap-turing the actual hydrodynamic behavior of a working LHP needs to be improved, hampering the de-velopment of precise modeling and design methodologies. This study on thermal performance alone needs to provide a comprehensive picture. Therefore, using visualization is important because research on visualization of working fluid behavior in two phases still needs to be completed. Therefore, neu-tron radiography is used in this experiment to observe the boiling and fluid dynamics in the heat pipe because it has advantages over other visualization methods. Copper material is used to develop the DE-LHP. The capillary wick used is made of stainless steel screen mesh. Deionized water with a 50% filling ratio is selected as the working fluid. To understand the flow behavior phenomenon under steady-state conditions, the heat load varies in a constant temperature range of 40-120oC. Three cartridge heaters simulate multiple heat sources and are controlled using a PID controller. The results show that the pro-posed DE-LHP can function well, accommodate multiple heat sources, and maintain stable performance over a wide range of constant temperatures. Neutron radiography images reveal essential details about the working fluid distribution during operation. The photos also show interesting findings, such as steam pulses and entrained working fluid in the vapor chamber and channels.